Characterization of trichome-specific BAHD acyltransferases involved in acylsugar biosynthesis in Nicotiana tabacum. (9th March 2022) - Chang, Aixia; Hu, Zhongyi; Chen, Biao; Vanderschuren, Herve; Chen, Ming; Qu, Yafang; Yu, Weisong; Li, Yangyang; Sun, Huiqing; Cao, Jianmin; Vasudevan, Kumar; Li, Chenying; et al.
Abstract: Glandular trichomes of tobacco ( Nicotiana tabacum ) produce blends of acylsucroses that contribute to defence against pathogens and herbivorous insects, but the mechanism of assembly of these acylsugars has not yet been determined. In this study, we isolated and characterized two trichome-specific acylsugar acyltransferases that are localized in the endoplasmic reticulum, NtASAT1 and NtASAT2. They sequentially catalyse two additive steps of acyl donors to sucrose to produce di-acylsucrose. Knocking out of NtASAT1 or NtASAT2 resulted in deficiency of acylsucrose; however, there was no effect on acylsugar accumulation in plants overexpressing NtASAT1 or NtASAT2 . Genomic analysis and profiling revealed that NtASAT s originated from the T subgenome, which is derived from the acylsugar-producing diploid ancestor N. tomentosiformis . Our identification of NtASAT1 and NtASAT2 as enzymes involved in acylsugar assembly in tobacco potentially provides a new approach and target genes for improving crop resistance against pathogens and insects. Abstract : ASAT1 and ASAT2 are trichome-specific acyltransferases in tobacco that sequentially catalyse two additive steps of acyl donors to sucrose to produce di-acylsucrose.